The fortune tellers of rue Daru - Gilmore, Olesya Salnikova (Berkley, 2026)
"Spirited twenty-something Zina and her secretive grandmother, Baba Valya, own a tearoom on rue Daru in Paris, where they have lived quietly since Zina's mother's untimely death. By day, the women serve tea, mostly to members of the bustling Russian émigré community, but when dusk falls, they divine fortunes and perform séances for their loyal clientele. Then the charming Princess Olga and her brother arrive, searching for answers about the disappearance of their father, the Grand Duke and cousin to the murdered last Tsar of Russia. Zina, eager to learn more about the spirit world and her powers, performs the séance. She is able to summon the Grand Duke, but to her horror, he starts to haunt the shop, and he seems to know something sinister about her mother's death. As Zina delves into her family's hidden past, dark secrets are unearthed, threatening Zina and her grandmother's found family, home, and tearoom, not to mention their very lives"-- Provided by publisher.